1990
DOI: 10.1159/000115308
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Descending Spinal Pathways in Prehensile Birds: Do Parrots Have a Homologue to the Corticospinal Tract of Mammals?

Abstract: In mammals, the supraspinal descending projections that influence distal limb muscles are the rubrospinal and corticospinal tracts. The former, which is found in other vertebrates, shows greater somatotopy in mammals that are 'dextrous' (e.g. monkeys) than those that are not (e.g. opossums). Similarly, the corticospinal tract, which is found only in mammals, has more extensive connections (i.e. direct corticomotoneural) in mammals that are dextrous than in mammals that are not. Descending spinal pathways have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
1
29
2
Order By: Relevance
“…The rather sparse cortical input to spinal cord and dorsal column nuclear complex in the lesser hedgehog tenrec should be considered in relation to the animal's phylogenetic position and the fact that similar projections have not been demonstrated in reptiles and birds (ten Donkelaar, 1982;Woodson and Kunzle, 1982;Webster et al, 1990). Our data do not support the views that ipsilateral pyramidal projections occur only in mammals with well developed contralateral corticospinal projections (Oliver et al, 1994) or in species with degenerated limbs (Nudo and Masterton, 1990).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The rather sparse cortical input to spinal cord and dorsal column nuclear complex in the lesser hedgehog tenrec should be considered in relation to the animal's phylogenetic position and the fact that similar projections have not been demonstrated in reptiles and birds (ten Donkelaar, 1982;Woodson and Kunzle, 1982;Webster et al, 1990). Our data do not support the views that ipsilateral pyramidal projections occur only in mammals with well developed contralateral corticospinal projections (Oliver et al, 1994) or in species with degenerated limbs (Nudo and Masterton, 1990).…”
Section: Discussioncontrasting
confidence: 63%
“…There is a huge difference in the number of corticospinal fibers between the tenrec and other mammals investigated, even if one compares just the pyramidal fibers descending ipsilaterally, i.e., the fibers coursing along the dominant side in Et and the non-dominant side in monkey (Bortoff and Strick, 1993), cat (Satomi et al, 19891, rat (Vahlsing and Feringa, 1980;Liang et al, 19911, and opossum (Cabana and Martin, 1985). The poor representation of the corticospinal system in Et should be considered in relation to the tenrec's phylogenetic position (Eisenberg, 1981;Piccinini et al, 1991) and the fact that a corresponding system may be entirely lacking in birds (Webster et al, 1990) and reptiles (Ten Donkelaar, 1982;Woodson and Kunzle, 1982;Follett, 1989).…”
Section: Corticospinal Projectionsmentioning
confidence: 99%
“…The red nucleus in birds projects to all levels of the spinal cord (Wild et al, 1979;Cabot et al, 1982: Webster andSteeves, 1988;Webster et al, 1990), predominantly contralaterally, so that, even though HA does not appear to project beyond midcervical levels, its influence may be relayed to all spinal levels via the HA-rubrospinal pathway. What kind of influence this might be is currently unknown, partly because there is no information on the role of the red nucleus in birds in either (Wild et al, 1979) might suggest a role in either the control of sensory input and/or the modulation of spinal refex circuitry via spinal interneurons, rather than one concerned directly with motor control.…”
Section: Relation To Cells Of Origin Of Descending Brainstem Pathwaysmentioning
confidence: 99%
“…Likewise in psittacines, Kalischer's (1905) ''cortico-septo-spinalis' ' and Zecha's (1962) ''pyramidal tract'' were both described as occupying a position at the base of the medulla corresponding to that of the pyramid in mammals and were observed to enter the upper cervical spinal cord (Kalischer) or to terminate chiefly in the dorsal column nulcei (Zecha). However, no study using retrograde tracing techniques has thus far confirmed a telencephalic origin of any long descending tract that might enter the spinal cord in birds, including parrots (Cabot et al, 1982;Gross and Oppenheim, 1985;Webster and Steeves, 1988;Webster et al, 1990). This negative evidence and the lack of any detailed or comprehensive modern account of the projections of the rostral Wulst in birds has apparently contributed to the general view, mentioned above, that pallial projections to the spinal cord are present only in mammals (e.g., Nudo and Masterton, 1988).…”
mentioning
confidence: 99%
“…Thus, the classic anterograde and retrograde degeneration techniques were replaced by tracttracing techniques based on the retrograde transport of macromolecules. In particular, horseradish peroxidase (HRP) backlabeling of the cells of origin of descending supraspinal pathways was widely applied in agnathans (Ronan, 1989), cartilaginous fishes (Smeets and Timerick, 1981;Cruce et al, 1999), bony fishes (Oka et al, 1986;Prasada Rao et al, 1987), lungfishes (Ronan and Northcutt, 1985), amphibians (ten Donkelaar et al, 1981;, reptiles (ten Donkelaar et al, 1980;Woodson and Kü nzle, 1982;Newman et al, 1983), birds (Cabot et al, 1982;Gross and Oppenheim, 1985;Webster et al, 1990), and mammals (see Kuypers, 1981;Nudo and Masterton, 1988).…”
mentioning
confidence: 99%